Strategi Pengembangan Wilayah Berbasis Ekonomi Lokal di Pesisir Desa Mekar Indah Kecamatan Buki Kabupaten Kepulauan Selayar - Albab, Nurul Istiqamah Ulil (Jurnal Wilayah dan Kota, 2023)
According to Regional Regulation Number 5 of 2012 concerning Selayar Islands Regency Spatial Planning for 2012-2032, it is explained that Mekar Indah Village is included in the coastal area where the majority of the population relies on marine products by working as fishermen, especially for people who live in coastal areas. . The activities carried out by fishermen in this village every day are to catch fish and sell them to the villagers. Based on research results, Mekar Indah Village has a potential that can be developed to improve the welfare of its community, one of the potentials found in Mekar Indah Village is the potential for natural resources in the fisheries sector. However, the community has not been able to manage these resources optimally, due to the lack of knowledge of the use of coastal resources, as well as the low quality of human resources to manage these fishery products. Seeing the problems above, efforts are needed to empower coastal communities. The analytical method used in this research is the triangulation analysis method. The concept of empowering coastal communities to minimize the problems that occur in coastal areas can be an effort to develop local economic-based coastal areas in Mekar Indah Village, namely increasing knowledge and skills, fostering innovation in fish processing, training in the use of the latest technology, fisheries cooperatives, establishing partnerships for product marketing.